Many-channel microscopic cluster model of 8Be: S-factors - Zhaba, Vasyl; Lashko, Yuliia; Vasilevsky, Victor (My University, 2025)
Abstract: We investigate low-energy astrophysical S factors for reactions proceeding through the 8Be compound system with entrance channels p+7Li, n+7Be, and d+6Li. Using the same microscopic many-channel three-cluster framework as in our previous study of the high-lying 8Be spectrum, we calculate S(E) for 7Li(p,α)4He, 7Be(n,α)4He, 7Be(n,p)7Li, 6Li(d,α)4He, 6Li(d,p)7Li, and 6Li(d,n)7Be in the energy range relevant for primordial and stellar nucleosynthesis. For the mirror pair 7Li(p,α)4He / 7Be(n,α)4He and for 7Be(n,p)7Li, the calculated S factors reproduce both the absolute scale and the low-energy trends of the experimental data within their quoted uncertainties, whereas the absolute S factors for the deuteron-induced channels on 6Li are underestimated at low energy, consistent with the shifted 6Li+d threshold and the absence of a broad subthreshold 2^+ structure in the present implementation. A partial-wave analysis identifies the dominant J^π contributions in each channel and relates them to specific 8Be resonances, while demonstrating that cluster polarization, previously shown to be crucial for the 8Be spectrum, is likewise essential for the normalization and energy dependence of several S factors. Evaluating S(E) at appropriate Gamow energies, we obtain a hierarchy of reaction channels that quantifies the relative importance of neutron- and deuteron-induced processes for the production and destruction of 7Li and 7Be.
Keywords: microscopic cluster model; resonating group method; 8Be; astrophysical S factors; p+7Li; n+7Be; d +6Li reactions; lithium nucleosynthesis; cosmological lithium problem